False failures, real distrust: the impact of an infrastructure failure deepfake on government trust - Ahmed, Saifuddin; Masood, Muhammad; Bee, Adeline Wei Ting; Ichikawa, Kei (Frontiers in Psychology, 2025)
Deepfakes today represent a novel threat that can induce widespread distrust more effectively than traditional disinformation due to its potential for greater susceptibility. In this study, we specifically test how individuals' exposure to deepfakes related to public infrastructure failures is linked to distrust in government, with their cognitive reflection and education possibly acting as a buffer. Using experimental data from the United States and Singapore, our findings indicate that exposure to deepfakes depicting a localized infrastructure failure, i.e., the collapse of a public bridge, heightens distrust in government among American participants but not Singaporeans. Additionally, education was found to be a significant moderator such that higher education levels is associated with lower political distrust when exposed to deepfakes. The role of deepfakes in influencing distrust in the government and the broader implications of these findings are discussed.